Microwave irradiation of gallium arsenide - Red'ko, R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
To study an influence of the microwave irradiation on a spectrum of defect states in semiconductor compound GaAs, we used measurements of luminescence spectra within the range 0.5 to 2.04 eV at 77 К before and after long (up to 13 min) treatments in air in the operation chamber of a magnetron at the frequency 2.45 GHz and surface power density 7.5 W/cm2. It was obtained that, already on the smallest irradiation exposure, the spectra of defects in researched samples essentially changed as well as concentrations of local centers changed. A "transfer" of intensity from the band with the peak 1.04 eV to the that peaking at 1.3 eV was observed.